Comparative Study of Factors Affecting Dependency of Households on Dry Deciduous Forest in Shivpuri, Madhya Pradesh (India). Issue 1 (December 2021) - Pandey, H; Rajmohan, S; Bung, S; Bhutia, S Y
Abstract: The rural and tribal communities of Madhya Pradesh's Shivpuri District depend on forest resources for meeting their domestic energy needs, forest products, and employment. Under Green India Mission, households were randomly selected and surveyed. The data of 61 households from 3 villages of Satanwada range (dry deciduous forest) and 131 households from 4 villages in Pichhore range (dry deciduous scrub forest) was collected through semi-structured questionnaire interviews and direct observation. Generalised Linear Model was used to determine the major factors affecting fuelwood collection. The study revealed the factors affecting the amount of fuelwood collection in Satanwada and Pichhore. Family size of households near to the forest negatively affected the amount of fuelwood collected; opportunity cost of fuelwood collection was lower for them than for families living further away from the forest in Satanwada. In Pichhore, LPG consumption reduced the amount of fuelwood collected, while cow dung complimented the quantity of fuelwood collected. Since the availability of fuelwood was scarce, alternate energy resources became determining factors of the amount of fuelwood collected. In both ranges, the distance of the forest from households had a positive effect on the quantity of fuelwood consumed due to higher opportunity cost and degradation of adjacent forests. The study also revealed a strong correlation between the sampled population percentage of women in villages and the sampled village cattle count. The study also showed the difference of fuelwood collection in Satanwada (8.8 ± 0.6 kg) and Pichhore (6.8 ± 0.4 kg) suggesting that forest degradation correlates with lesser utilisation of forest resources. Hence, the study justifies the need of synergy between public rural provisions of alternative fuel sources with afforestation programs.